The Development of the Fear of COVID-19 Pandemic Scale and the Pandemic Uncertainty Scale. - ÇAL, Ayşe; AYDIN AVCI, İlknur; KABATAŞ YILDIZ, Mükerrem (Journal of Nursology, 2022)
Objective: This study aims to develop two separate measurement tools specific to Turkish culture to evaluate the fear of COVID-19 pandemic and the pandemic uncertainty. Methods: It is a methodologically designed study. A draft form for both scales was prepared by the researchers in line with the relevant literature. The forms revised in line with the expert opinions were administered to 386 university students and their families between May and July 2020 during the COVID-19 pandemic. The data were analyzed using Statistical Package for the Social Sciences Version 22 and Amos 23 program. The Cronbach's alpha coefficient was calculated, and the exploratory and confirmatory factor analyses and the Pearson correlation analysis were conducted to test construct validity. Results: The Fear of COVID-19 Pandemic Scale was found to be acceptable with 1 factor and 8 items, and the Pandemic Uncertainty Scale was found to be acceptable with 3 factors and 18 items. The Cronbach's alpha of the Fear of COVID-19 Pandemic Scale was found to be 0.92. The Cronbach's alpha of the Pandemic Uncertainty Scale was found to be 0.90 and that of the factors was between 0.86 and 0.89. Conclusion: It was determined that both scales are reliable and can be used within the Turkish context.